اختلاف اور مخالفت کی مروجہ صورتوں کے محرکات و عوامل کا تحقیقی جائزہ: A Research Study on the Motivations and Factors Behind the Manifestations of Disagreement and Opposition - Dr Noreen Naz; Saima Anwar; Ghulam Dastgir Ahmad (International Research Journal of Arabic and Islamic Studies, 2024)
This research study delves into the intricate motivations and underlying factors that drive the manifestations of disagreement and opposition within various contexts. The research aims to uncover the psychological, social, and cultural aspects that contribute to individuals or groups expressing dissenting views or opposing positions. By employing a multi-disciplinary approach, including psychological theories, sociological frameworks, and cultural analysis, this study seeks to provide a comprehensive understanding of why and how disagreement and opposition emerge. Through qualitative and quantitative methodologies, including surveys, interviews, and content analysis, the study will examine real-life scenarios and perceptions to identify common patterns, key influencers, and potential mitigating strategies. The findings from this research are expected to shed light on the complexities of disagreement and opposition, offering insights that can inform decision-making processes, conflict resolution strategies, and promote constructive dialogue in diverse settings.